Fungal lipid biochemistry distribution and metabolism - Weete, John D.; Weber, Darrell D. [cont.]; Hess, William M. [cont.] (New York Plenum Press, 1974)
Vol. 1, Fungal lipid biochemistry by John D. Weete. 1974
Keywords: Fungi -- Physiology; Lipids